KOMPETISI DAN WORKSHOP METAVERSE UNTUK SMA/SMK DI JABODETABEK - Haris., M.TI, Darius Andana; Setiawan, Jerry; Cuang, Edgar Johan (Jurnal Bakti Masyarakat Indonesia, 2024)
The development of information technology makes it mandatory for the young generation in Indonesia to be digital technology literate. Digital literacy, especially in the use of various technological devices, is not only the domain of adults. The concept of the Metaverse has moved closer to reality thanks to recent technological advances. Within the Metaverse, individuals can engage in the digital environment in a more immersive and unified way. One of the key elements of the Metaverse concept is interconnectedness, where multiple digital platforms and environments can connect seamlessly, facilitating an individual's seamless movement from one experience to another. In line with technological developments, the interests of the younger generation in Indonesia need to be utilized. As a form of effort to address partners' concerns about the lack of young people interested in VR, this competition and workshop was held. The Metaverse competition and workshop are community service activities carried out by the Game Development Lab from the Faculty of Information Technology, Tarumanagara University (FTI UNTAR). The targets of this activity are high school/vocational school students in the Jabodetabek area. This activity was carried out over 2 days, where the first was an introduction and training on Metaverse content creation and the second day was a Metaverse competition. Each participant created Metaverse content and is assessed by a team of judges who come from partners who have collaborated, in this case OmniVR. Participants compete in groups consisting of 3 people. A total of 11 groups from 8 schools competed and have produced their own metaverse products. The winner has been determined and the PKM implementation is running smoothly. ABSTRAK: Perkembangan teknologi informasi menjadikan generasi muda di Indonesia wajib melek teknologi digital. Literasi digital, terutama dalam pemanfaatan berbagai perangkat teknologi, tidak hanya menjadi domain orang dewasa. Konsep Metaverse telah semakin mendekati realitas berkat kemajuan teknologi baru-baru ini. Di dalam Metaverse, individu dapat terlibat dalam lingkungan digital secara lebih mendalam dan menyatu. Salah satu elemen kunci dari konsep Metaverse adalah saling terhubung, di mana berbagai platform dan lingkungan digital dapat terhubung dengan mulus, memfasilitasi perpindahan individu dari satu pengalaman ke pengalaman lain tanpa hambatan. Sejalan dengan perkembangan teknologi, minat generasi muda di Indonesia perlu digunakan. Sebagai salah satu bentuk upaya menangani keresahan mitra dengan kurangnya generasi muda yang tertarik kearah VR, diadakanlah kompetisi dan workshop ini. Kompetisi dan workshop Metaverse merupakan kegiatan pengabdian kepada masyarakat yang dilaksanakan oleh Lab Game Development dari Fakultas Teknologi Informasi Universitas Tarumanagara (FTI UNTAR). Sasaran dari kegiatan tersebut yaitu siswa SMA/SMK di wilayah Jabodetabek. Kegiatan ini telah dilaksanakan dalam waktu 2 hari di mana pertama merupakan pengenalan dan pelatihan pembuatan konten Metaverse dan hari kedua adalah kompetisi Metaverse. Setiap peserta membuat konten Metaverse dan dinilai oleh tim juri yang berasal dari mitra yang telah bekerja sama, dalam hal ini adalah OmniVR. Peserta berlomba dalam bentuk kelompok yang terdiri dari 3 orang. Sebanyak 11 kelompok dari 8 sekolah berlomba dan telah menghasilkan produk metaversenya sendiri. Pemenang telah ditentukan dan pelaksanaan PKM berjalan lancar.